Application of cellular automata simulation to truss structure design - Kita, E.; Toyoda, T.; Tamaki, T.; Xie, Y. M. (Computer Assisted Methods in Engineering and Science, 2004)
In the cellular automata simulation, the object under consideration is divided into small cells and the simulation is performed according to the local rule which is defined as the local relationship among cells. In this paper, the concept of cellular automata is applied to the design scheme of truss structures. First, truss elements are considered as the cells of the cellular automata and the local rule is derived from the optimization problem. The objective functions are defined to minimize the total weight of the structure and to obtain even stress distribution in the whole structure. The constraint conditions are introduced in order to define the local rule. The present method is applied to the design of the plane and the three-dimensional truss structures such as Schwedler and Lamella Domes. The convergence histories of the total weight and the mean and the maximum stresses are shown in order to discuss the property of the present method.